Contribution of Hydrolysis and Drying Conditions to Whey Protein Hydrolysate Characteristics and In Vitro Antioxidative Properties - Thanyaporn Kleekayai; Aileen O'Neill; Stephanie Clarke; Niamh Holmes; Brendan O'Sullivan; Richard J. FitzGerald (MDPI AG, 2022)
During the generation of functional food ingredients by enzymatic hydrolysis, parameters such as choice of enzyme, reaction pH and the drying process employed may contribute to the physicochemical and bio-functional properties of the resultant protein hydrolysate ingredients. This study characterised the properties of spray- (SD) and freeze-dried (FD) whey protein hydrolysates (WPHs) generated using Alcalase® and Prolyve® under pH-stat and free-fall pH conditions. The enzyme preparation used affected the physicochemical and antioxidative properties but had no impact on powder composition, morphology or colour. SD resulted in spherical particles with higher moisture content (~6%) compared to the FD powders (~1%), which had a glass shard-like structure. The SD-WPHs exhibited higher antioxidative properties compared to the FD-WPHs, which may be linked to a higher proportion of peptides <1 kDa in the SD-WPHs. Furthermore, the SD- and FD-WPHs had similar peptide profiles, and no evidence of Maillard reaction product formation during the SD processing was evident. The most potent in vitro antioxidative WPH was generated using Alcalase® under free-fall pH conditions, followed by SD, which had oxygen radical absorbance capacity and Trolox equivalent (TE) antioxidant capacity values of 1132 and 686 µmol TE/g, respectively. These results demonstrate that both the hydrolysis and the drying process impact the biofunctional (antioxidant) activity of WPHs.